Caracterização da Savana Estépica Parque no baixo médio São Francisco, Bahia, Brasil - Damascena, Leilton Santos (2011)
The Caatinga vegetation is formed by several physiognomic units including the Steppic Savannah Parkland (Tp), which is regarded as the unit more typical Steppic Savannah. Our objectives were: to analyze the hierarchical structure of the conceptual classification of the vegetation, inventory the plant species and describe their phytosociological relationships in order to assess the unique floristic and structural characterization of abiotic factors, in addition to developing the mapping of Tp to region of the lower middle São Francisco. For this, was developed the conceptual organization of classification systems based on this influence for the formation of groups, was prepared after the ratings on the principal components. Phytosociology was based on collecting data on floristic and structural field, to aid comparison with other studies conducted in the Stepic Savannah. Mapping was conducted in two regions, Rodelas and Juazeiro, based on classification techniques (MAXVER, Minimum Distance, Simple Slicing) for two seasons seasonally opposed to more precise delineation of this vegetation unit. This study showed that: a) The conceptual organization of the classification systems demonstrated that concepts related to structure dominated the segregation units of vegetation systems, where the floristic data are not used as information for determining the boundaries of groups. b) The floristic and phytosociological analysis presented, Tp consists of a canopy full of gaps, containing shrubs, herbs, grasses and sometimes trees partially covering the stony soil. This physiognomy is characterized by spaced pattern of nanophanerophytes with a pseudo-ordination, where clusters of woody plants developed on a dense covering of hemicriptophytes and chamaephytes. The shrubs are mainly Poincianella pyramidalis (Tul.) L.P. de Queiroz, Jatropha molissima Baill., Cnidoscolus quercifolius Pohl and Aspidosperma pyrifolium Mart., the herbaceous layer is dominated by Aristida sp. The soil is shallow and rocky with little organic matter. c) The mapping of Rodelas area showed the most typical characteristics and the greatest area of physiognomy. In another hand, Juazeiro area was fragmented and permeated by transitions areas with anthropic physiognomy. The Steppic Savannah Parkland is an unit distinct from other vegetation types by the existence of small phanerophytes species groups in a continuous Aristida field.